THE NEXUS OF INDUCING DEVELOPMENT: MEASURE PATH DISCOURSES IN INDONESIA’S DYNAMIC LANDSCAPE - Ivan Sudibyo (MESP–FEB UNS, 2024)
The research objective underscores the importance of human capital, innovation, and research in fostering sustainable economic growth, with a focus on principal variables such as human capital development (measured by HDI), innovation and competitiveness (driven by FDI inflows), R&D expenditure, and employment dynamics. The research results reveals that FDI, R&D spending, and employment significantly impact TFP growth, with FDI inflows identified as a push driver of TFP growth by enhancing innovation and competitiveness. This research applies the research methodology ARDL model to delve into the factors that influence Total Factor Productivity (TFP), drawing on Romer’s theory of endogenous growth. The research results also highlight the role of R&D expenditure in boosting TFP, emphasizing the need for a supportive environment for research and innovation. The labor force is also found to contribute significantly to TFP. The research further explores the interaction between the labor force and R&D, suggesting the need for policies that support both workforce development and innovation for sustained prosperity. The study also incorporates the concept of employment elasticity with respect to growth as a measure of inclusive development. It concludes by advising stakeholders to prioritize the promotion of FDI inflows, entice R&D spending, and treatise labor force issues to enhance TFP growth and ensure long-term economic prosperity. This underscores the importance of stakeholders’ cooperation in leveraging investments for long-term economic prosperity.